Systemic Exophiala equina infection in an Eastern box turtle (Terrapene carolina carolina): a case report and literature review - Barrantes Murillo, Daniel Felipe; Anderson, Stephanie; Capobianco, Christian; Lewbart, Gregory A.; Wiederhold, Nathan P.; Cañete-Gibas, Connie F.; Negrão Watanabe, Tatiane Terumi (Frontiers in Veterinary Science, 2023)
Phaeohyphomycosis is an infection caused by melanized fungi. This disease has been reported in several animal species including invertebrates, cold-blooded vertebrates, mammals, and humans. Melanized fungi have similar phenotypical features and confirmation requires culture and molecular diagnostics. To exemplify this we present a case of a 333 g adult of unknown age, free-ranging, male Eastern box turtle (Terrapene carolina carolina) that was referred to the Turtle Rescue Team at North Carolina State University for evaluation multilobulated masses occupying the entire left orbit and at the right forelimb on the plantarolateral aspect of the foot. A fine needle aspirate cytologic examination of the mass on the right forelimb revealed large numbers of inflammatory cells and fungal organisms. Histopathology of the skin biopsies from the right forefoot was consistent with phaeohyphomycosis. A course of antifungal medication was started (Fluconazole 21 mg/kg loading dose IV then 5 mg/kg PO SID q 30 days). Due to concern for the patient’s quality of life and the lack of a curative treatment plan, humane euthanasia was elected. Gross postmortem examination confirmed the presence of multiple coelomic masses similar in appearance to those observed in the left orbit and right forefoot indicating disseminated phaeohyphomycosis. A swab of the periocular mass was submitted for fungal culture and phenotypic identification. The isolate was later identified as Exophiala equina through a combination of phenotypic characterization and sequencing of the ITS region of the nuclear rDNA. Exophiala is a genus in the family Herpotrichiellaceae, order Chaetothyriales and is considered an opportunistic “black yeast” causing infection in aquatic invertebrates, fish, amphibians, reptiles, and mammals including humans. Exophiala equina is infrequently reported in animals, with only three cases in the literature including the herein report.